La modificación constitucional del derecho a la nacionalidad peruana - Abugattãs, Gattãs (2020)
In 2018, article 52 of the Political Constitution of Peru of 1993, which regulates the ways in which Peruvian nationality is acquired and granted, was modified. With this amendment, will be considered Peruvians «by birth», among other cases, not only those persons born abroad of a Peruvian father or mother who are registered during their minority in the corresponding registry, but also those who, in that condition, are registered during their age of majority.This paper explains what should be understood by nationality; develops the Peruvian constitutional regulation of nationality, detailing the amendment process of article 52 of the Constitution; to finally make a critical analysis of this reform.The purpose of this paper is to demonstrate that there is no justification for establishing differences between persons born abroad of a Peruvian father ormother who are registered during their minority in the corresponding registry, who acquire nationality «by birth», and those who, in that condition, areregistered during their age of majority, who —before the amendment— were granted nationality for exercising the «right of option», which did not allowthem access to all constitutional rights role.